Renewing philosophy - Putnam, Hilary (London : Harvard University Press, 1992)
A renewal of philosophy is precisely the point of this book, drawn from the 1989 Gifford Lectures by one of America's most distinguished philosophers. In a wide-ranging survey of major issues, Hilary Putnam proposes a revitalized approach to philosophical questions. Putnam contests the view that only science offers an appropriate model for philosophical inquiry, that only a metaphysics congruent with physics suffices, while questions of art and ethics, love, death, and
Religion must be set aside due to the lack of an adequate language or perspective. His discussion of topics from artificial intelligence to natural selection, and of reductive philosophical views derived from these models, identifies the insuperable problems encountered by philosophy when it ignores the normative or attempts to reduce it to something else. Looking for a better way of doing philosophy, Putnam takes up the problems posed by religious discourse - often
Viewed by philosophers as prescientific and primitive, an unlikely survivor from the age of superstition. In luminous pages on Wittgenstein, he refutes this view and shows how the philosopher's frequently misunderstood forays into religious discourse actually open up philosophy to a broad range of practical, moral, and political issues. In closing, Putnam considers Dewey, who occupies a middle ground between metaphysics and skepticism, and whose broadly epistemological
Arguments in favor of democracy this book eloquently advances. Written in Putnam's characteristically lucid and engaging style, this is a compelling call to reject the confusions and reductions that obscure the human issues which it has always been philosophy's highest goal to articulate
The project of artificial intelligence -- Does evolution explain representation? -- A theory of reference -- Materialism and relativism -- Bernard Williams and the absolute conception of the world -- Irrealism and deconstruction -- Wittgenstein on religious belief -- Wittgenstein on reference and relativism -- A reconsideration of Deweyan democracy
Based on the Gifford lectures delivered at the University of St. Andrews in fall, 1990
Includes bibliographical references and index
Keywords: Philosophy; Philosophy and science; Philosophy; Aufsatzsammlung